Effect of Ischemic Oppression on Trigger Points of Patients with Myofascial Pain Syndrome - Xinjian LI; Nanjun CHEN; Jianyu YANG; Enming ZHANG; Zheng GAO; Zhenmin BAI (康复学报)
Objective:To observe the effect of ischemic oppression on trigger points of patients with myofascial pain syndrome (MPS).Methods:A total of 20 patients with cervical and shoulder myofascial pain syndrome were randomly divided into control group and treatment group, with 10 patients in each group. The control group was treated with healthy education, and the treatment group was treated with the therapy of ischemic oppression on trigger points based on the control group. Firstly, we release the upper trapezius bundle of patients by gradually increasing the vibration frequency through Booster Pro3 fascia gun to relax and activate the upper trapezius muscle, and then we treat the patients with MPS by the method of ischemic compression on pain trigger points, once time per day, continuous treatment for two weeks. Before and after treatment, the cervical joint mobility and muscle strength were measured by the tester instrument of muscle and spinal mobility, the pain degree of neck and shoulder was evaluated by visual analogue scale (VAS), the level of cervical dysfunction was evaluated by neck disability index (NDI).Results:Compared with before treatment, the left and right muscle strength increased significantly in the treatment group after the first treatment, the range of motion (forward flexion), left and right muscle strength increased significantly in the treatment group after treatment for two weeks, VAS scores at the left flexion, right flexion and right rotation and NDI scores decreased significantly, with statistically significant differences (P<0.05). Compared with the control group, the range of motion (forward flexion), left and right muscle strength of the treatment group after treatment for two weeks were higher, the VAS scores at the left flexion, right flexion and right rotation and NDI scores of the treatment group after treatment for two weeks were lower, with statistically significant differences (P<0.05).Conclusion:The therapy of ischemic oppression on trigger points can effectively improve the range of motion of the neck joints, left and right muscle strength of MPS patients, relieve the stiffness, discomfort and pain of neck muscles, and improve the status of cervical dysfunction, which is worthy of clinical promotion and application.